2020
DOI: 10.1002/mp.14368
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of radiomic features in magnetic resonance imaging of glioblastoma: Test–retest and image registration analyses

Abstract: To assess the repeatability of radiomic features in magnetic resonance (MR) imaging of glioblastoma (GBM) tumors with respect to test-retest, different image registration approaches and inhomogeneity bias field correction. Methods: We analyzed MR images of 17 GBM patients including T1-and T2-weighted images (performed within the same imaging unit on two consecutive days). For image segmentation, we used a comprehensive segmentation approach including entire tumor, active area of tumor, necrotic regions in T1-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 68 publications
3
47
0
Order By: Relevance
“…Additionally, the findings suggested that both intensity and texture features demonstrated higher variability as compared with the shape features. These findings are in line with previous repeatability (5) and reproducibility studies (10,11), where intensity and texture features have been found to be sensitive to subtle variations in test-retest scans, as well as image variations across sites and scanners. Both texture (describing heterogeneity measures from gray-level co-occurrence matrix) and intensity features (describing the distribution of intensity values) are dependent on the actual per-voxel intensity values within the region of interest and may yield substantially different measurements if they are not appropriately normalized in some fashion before downstream analysis.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, the findings suggested that both intensity and texture features demonstrated higher variability as compared with the shape features. These findings are in line with previous repeatability (5) and reproducibility studies (10,11), where intensity and texture features have been found to be sensitive to subtle variations in test-retest scans, as well as image variations across sites and scanners. Both texture (describing heterogeneity measures from gray-level co-occurrence matrix) and intensity features (describing the distribution of intensity values) are dependent on the actual per-voxel intensity values within the region of interest and may yield substantially different measurements if they are not appropriately normalized in some fashion before downstream analysis.…”
supporting
confidence: 91%
“…Multiple efforts are currently underway to address some of the practical challenges associated with generalizability of radiomic features. These include attempts to study radiomic variability across large multisite data (4), controlled test-retest data (5), and phantom studies (6). Most of these attempts so far have been in the pursuit of identifying a set of radiomic features that are both repeatable and reproducible across different image acquisition, preprocessing, segmentation, and radiomic feature extraction pipelines.…”
mentioning
confidence: 99%
“…For MRI radiomics, such a unit does not exist which poses problems due to inter-and intra-scanner variability. Multiple pre-processing methods have been developed, though not all radiomics features were shown to be robust between different pre-processing approaches [57][58][59]. This calls for a generalized pre-processing pipeline and focus on features that are shown to be robust.…”
Section: Discussionmentioning
confidence: 99%
“…For each mask, 348 features were extracted using the MaZda software. These included histogram (9), cooccurrence matrix (220), run-length matrix (20), gradient (5), autoregressive (5), geometrical (73) and wavelet (16) features. Details about these features are provided elsewhere and beyond the scope of this work.…”
Section: Texture Features Extractionmentioning
confidence: 99%